Technological and organizational innovations in offices and the impacts on the quality of work life (Cadernos de Psicologia Social do Trabalho, 2012)
This study aimed to identify the new requirements of work in offices, in the current production scenario, driven by technological and organizational innovations, and their impact on the quality of work life. The theoretical framework was based on the assumptions of Ergonomics of Activity, and the method was based on Ergonomic Work Analysis (EWA). The research, which has a qualitative approach, used individual semi-structured interviews, with the participation of thirty professionals from a large Brazilian financial institution, and the data were analyzed using the software Alceste. The results indicated that respondents recognize the importance of technological innovations to carry out their activities, but they associate to them the advent of new requirements, mainly due to the intensification and greater complexity and control of work, resulting in an increased human cost of work.